2007
DOI: 10.1007/s11610-007-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

The chevron osteotomy for correction of hallux valgus

Abstract: Introduction: The chevron osteotomy has become widely accepted for correction of mild and moderate hallux valgus deformities. The purpose of this study was to present the evolution of the chevron osteotomy at one institution over a period of 12 years.Methods: Between April, 1991 and September, 1992, fifty-two consecutive patients with mild to moderate hallux valgus deformity underwent sixty-six distal chevron osteotomies at our institution. This was followed by 85 patients with 100 feet in the period from 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…39,40 Our comparison of the results on the basis of the patient's age at diagnosis (< 50 years vs ≥ 50 years) revealed more favourable clinical and radiological outcomes in those aged < 50 years, but these differences were not statistically significant (Table III).…”
Section: Discussionmentioning
confidence: 82%
“…39,40 Our comparison of the results on the basis of the patient's age at diagnosis (< 50 years vs ≥ 50 years) revealed more favourable clinical and radiological outcomes in those aged < 50 years, but these differences were not statistically significant (Table III).…”
Section: Discussionmentioning
confidence: 82%
“…1,7,10,17 Several authors have stated that distal chevron osteotomy should be limited to patients who have an intermetatarsal angle (IMA) of less than 15 degrees and a hallux valgus angle (HVA) of less than 30 degrees. 10,14,17 In this retrospective study, we have analyzed the clinical and radiographic results obtained in 52 bunion deformities with an IMA up to 20 degrees and an HVA up to 40 degrees, surgically treated by distal chevron osteotomy plus lateral release and adductor tenotomy with the additional aim to better define the indication for this surgical procedure. With regard to the IMA evaluated at diagnosis, we divided our patients into two groups (angle Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in some cases at followup the value of this angle was slightly above the normal value. Some authors 2 recommend that chevron osteotomy should be performed only for patients younger than 50 years of age; other authors 14,17 have reported that this surgical procedure may be performed even in elderly patients. We divided our results on the basis of the patient's age at diagnosis, less and more than 50 years old, and did not observe any significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…The modified chevron osteotomy seems to produce anatomic correction similar to that of our technique and has better stability at the osteotomy site; however, it does not prevent dorsal angulation or medial or lateral tilting or shortening. Trnka et al 5 reported intraoperative instability in four of 46 chevron osteotomies. We have further modified the technique to provide even greater stability at the osteotomy site.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Malunion also has been reported at the osteotomy site. 5 Johnson et al 2 reported excellent relief of pain and cosmetic correction with the modified chevron osteotomy technique in 26 feet (18 patients). The modified chevron osteotomy seems to produce anatomic correction similar to that of our technique and has better stability at the osteotomy site; however, it does not prevent dorsal angulation or medial or lateral tilting or shortening.…”
Section: Introductionmentioning
confidence: 99%